Impact of CHF Correlations on DNBR of the TRIGA Mark II Research Reactor under different operational modes and burn-up conditions - HOSSEN, MD ALTAF (Communications in Physics, 2025)
Departure from Nucleate Boiling Ratio (DNBR) is a crucial thermal hydraulics safety parameter for nuclear reactors. Hence selecting appropriate DNBR correlation is vital for design, licence and operation. The Bernath, Misrak, and Tong correlations have been utilized in PARET/ANL code in this study to calculate DNBR in TRIGA Mark II research reactor during both steady state and transient conditions, spanning from the beginning of cycle (BOC) to 1000 MWD of operation life. The findings reveal that the Bernath correlation consistently yields the lowest values across all operational phases compared to the Misrak and Tong correlations. Remarkably, the results obtained from the Bernath correlation align with the recommendations put forth by the General Atomics (GA) and Safety Analysis Report. Consequently, it is deemed suitable for application throughout all modes of reactor operation.